Risk of Hemorrhagic Transformation after Mechanical Thrombectomy without versus with IV Thrombolysis for Acute Ischemic Stroke: A Systematic Review and Meta-analysis of Randomized Clinical Trials - Jazayeri, Seyed Behnam; Ghozy, Sherief; Hemmeda, Lina; Bilgin, Cem; Elfil, Mohamed; Kadirvel, Ramanathan; Kallmes, David F. (American Journal of Neuroradiology, 2024)
BACKGROUND: When treating acute ischemic stroke due to large-vessel occlusion, both mechanical thrombectomy and intravenous (IV) thrombolysis carry the risk of intracerebral hemorrhage.PURPOSE: This study aimed to delve deeper into the risk of intracerebral hemorrhage and its subtypes associated with mechanical thrombectomy with or without IV thrombolysis to contribute to better decision-making in the treatment of acute ischemic stroke due to large-vessel occlusion.DATA SOURCES: PubMed, EMBASE, and Scopus databases were searched for relevant studies from inception to September 6, 2023.STUDY SELECTION: The eligibility criteria included randomized clinical trials or post hoc analysis of randomized controlled trials that focused on patients with acute ischemic stroke in the anterior circulation. After screening 4870 retrieved records, we included 9 studies (6 randomized controlled trials and 3 post hoc analyses of randomized controlled trials) with 3241 patients.DATA ANALYSIS: The interventions compared were mechanical thrombectomy + IV thrombolysis versus mechanical thrombectomy alone, with the outcome of interest being any form of intracerebral hemorrhage and symptomatic intracerebral hemorrhage after intervention. A common definition for symptomatic intracerebral hemorrhage was pooled from various classification systems, and subgroup analyses were performed on the basis of different definitions and anatomic descriptions of hemorrhage. The quality of the studies was assessed using the revised version of Cochrane Risk of Bias 2 assessment tool. Meta-analysis was performed using the random effects model.DATA SYNTHESIS: Eight studies had some concerns, and 1 study was considered high risk. Overall, the risk of symptomatic intracerebral hemorrhage was comparable between mechanical thrombectomy + IV thrombolysis and mechanial thrombectomy alone (risk ratio, 1.24 [95% CI, 0.89–1.72]; P = .20), with no heterogeneity across studies. Subgroup analysis of symptomatic intracerebral hemorrhage showed a non-significant difference between 2 groups based on the National Institute of Neurological Disorders and Stroke (P = .3), the Heidelberg Bleeding Classification (P = .5), the Safe Implementation of Thrombolysis in Stroke-Monitoring Study (P = .4), and the European Cooperative Acute Stroke Study III (P = .7) criteria. Subgroup analysis of different anatomic descriptions of intracerebral hemorrhage showed no difference between the 2 groups. Also, we found no difference in the risk of any intracerebral hemorrhage between two groups (risk ratio, 1.10 [95% CI, 1.00–1.21]; P = .052) with no heterogeneity across studies.LIMITATIONS: There was a potential for performance bias in most studies.CONCLUSIONS: In this systematic review and meta-analysis, the risk of any intracerebral hemorrhage and symptomatic intracerebral hemorrhage, including its various classifications and anatomic descriptions, was comparable between mechanical thrombectomy + IV thrombolysis and mechanical thrombectomy alone.AISacute ischemic strokeHBCHeidelberg Bleeding ClassificationHIhemorrhagic infarctionICHintracerebral hemorrhageIVTintravenous thrombolysisLVOlarge-vessel occlusionMTmechanical thrombectomyPHparenchymatous hematomaRCTrandomized clinical trialsICHsymptomatic ICH